Pedestrian accessibility for people with reduced mobility and motor disabilities in the Plaza de Armas, Plaza Regocijo and Plaza San Francisco in the Historical Center of cusco. - Casapino Espinoza, Carlos Alberto (2021)
The present research aims to analyze pedestrian accessibility criteria based on national and international normative parameters in landmarks and itineraries within the Plaza de Armas, Plaza Regocijo and Plaza San Francisco of the Historic Center of the city of Cusco, department of Cusco. The study is relevant for observing the lack of a design in the public space with heritage and cultural values ​​with accessibility and mobility criteria, being also significant for users with mobility problems. The study analyzes how are the conditions of pedestrian accessibility in these spaces of the city through the diagnostic model of the accessibility of the buildings of patrimonial character of the University of Granada cited in the book of Universal Accessibility and Design for All of the Foundation ONCE and Fundación Arquitectura COAM, the results show the low level of regulatory compliance with these criteria, as well as the lack of accessible design for reduced mobility.